2017
DOI: 10.1001/jamaoto.2016.3669
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rates Using Individualized Bioselection Treatment Methods in Patients With Advanced Laryngeal Cancer

Abstract: The introduction of chemoradiation for advanced laryngeal cancer led to a major paradigm shift in treatment as an alternative to laryngectomy. Despite widespread adoption, survival rates have not improved and the original premise of matching neoadjuvant chemotherapy tumor response to determine subsequent treatment has not been followed. A unique approach incorporating a single cycle of neoadjuvant chemotherapy to select patients with advanced disease for either laryngectomy or concurrent chemoradiation was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 72 publications
4
47
2
3
Order By: Relevance
“…11 In our experience treating stage II laryngeal SCC at a tertiary academic center, we found a 2 and 5-year DSS of 91% and functional laryngeal preservation rate of 83%, consistent with previously published reports. 5-7 However, current Clinical Practice Guidelines in Oncology (NCCN Guidelines) for Head and Neck Cancer recommend no difference in the management of early stage (I vs. II) laryngeal malignancies.…”
Section: Discussionsupporting
confidence: 91%
“…11 In our experience treating stage II laryngeal SCC at a tertiary academic center, we found a 2 and 5-year DSS of 91% and functional laryngeal preservation rate of 83%, consistent with previously published reports. 5-7 However, current Clinical Practice Guidelines in Oncology (NCCN Guidelines) for Head and Neck Cancer recommend no difference in the management of early stage (I vs. II) laryngeal malignancies.…”
Section: Discussionsupporting
confidence: 91%
“…However, both induction chemotherapy (bioselective) for subsequent treatment selection and/or primary surgical intervention were associated with survival benefits that were greater than expected after adjustments for calculator‐estimated survival. Individualized treatment paradigms that integrate neoadjuvant bioselection are associated with a significant survival benefit and may account for the superior outcomes observed . These findings reinforce the need for updated survival calculators and provide further evidence that oncologic interventions and institution‐specific care are independent variables that affect the prognosis of patients with laryngeal cancer.…”
Section: Discussionmentioning
confidence: 59%
“…A recent paper published by Wolf et al suggested that superior survival rates could be achieved with a bioselective treatment approach that utilized a single cycle of neoadjuvant chemotherapy to select subsequent treatment. Good survival rates were also achieved in patients selected for primary surgery, and both neoadjuvant chemotherapy and primary surgery had better survival rates than with concurrent chemoradiotherapy.…”
Section: Treatment Factorsmentioning
confidence: 99%